Evaluating Students’ Competence in ESP: A Study in Naval Architecture Department of Politeknik Negeri Bengkalis - Antika, Rindilla; Asfina, Risda (ABEC Indonesia, 2024)
This study evaluates students' competence in English for Specific Purposes (ESP) in Naval Architecture Departmentof Politeknik Negeri Bengkalis. ESP subject is tailored to meet the specific language needs of students in specialized fields,aiming to enhance their communication skills in professional contexts. This study employed quantitative method, specificallya descriptive study. Using a purposive sampling technique, the samples of this study were 17 students of Naval ArchitectureDepartment of Politeknik Negeri Bengkalis. This study used a test to assess students' competence in English for navalarchitecture. Key areas of focus included types of ships, parts of ships, ship materials, and ventilation and coating system. Thefindings indicated a varying level of competence. The highest score was 77.5 and the lowest score was 47.5. Regarding theaverage scores of each topic, the highest average score was in the topic of types of ships (98.2), followed by parts of ships(65.9), ship materials (54.7), and ventilation and coating system (44.7). This study concludes that a good approach to teachingESP is essential for better preparing students for their professional careers especially in the shipping industry. As an implicationfor the lecturers of English for Naval Architecture, the topics of parts of ships, ship materials, and ventilation and coatingsystem, without neglecting other topics out of the focuses of this study, need to be learned more by the students of NavalArchitecture Department.